PANJI HITAM DARI ARAH TIMUR; Senjata Makan Tuan - Dadi Herdiansah (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2018)
One of the information spread about the arrival of the Mahdi priest was that he led the war troops by carrying a black banner from the east. This information comes from several histories in several hadith books. Pro kotra has occurred in response to this history. The Muslim groups who believe in the truth of this black banner tradition have flocked from all corners of the world to the Middle East conflict area which is believed and believed there is a group of mujahids carrying black banner as mentioned by the hadith. Even in the conflict area there was mutual claim between the factions that their faction was mentioned by the hadith carrying its black banner, so that even from one another, civil war was not inevitable in some places. But what is the origin of the hadith? This note is the adoptive writer to criticize the hadith by issuing all of his paths with the takhrīj al-hadīth method, Jarh wa ta'dīl and ‘Ilalu al-hadīth